Bioethics after Brexit: An opportunity to rationalize bioethics governance in the United Kingdom. (June 2018) - Montgomery, Jonathan
This article considers the shape of bioethics governance in Europe, noting the interplay between the institutions and laws of the Union and those of the Council of Europe. It reviews the structures of UK bioethics governance and identifies weaknesses that Brexit provides an opportunity to address. It notes the ambiguous relationship of UK bioethicists with European institutions and discusses the importance of soft power. It explores what the United Kingdom should do to maintain its influence. It advocates, first, improved coordination of governance organizations within the United Kingdom. Second, a more strategic approach to 'soft power' and UK involvement with international organizations, both within the European region and more widely. Finally, it proposes that the United Kingdom become a signatory to the Oviedo Convention in order to consolidate its connections with European values. These steps are suggested as mitigation for the loss of influence that Brexit might otherwise bring.